2016
DOI: 10.1002/slct.201600339
|View full text |Cite
|
Sign up to set email alerts
|

Ozonization to Upgrade Waste‐Derived Soluble Lignin‐Like Substances to Higher Value Products

Abstract: Soluble biobased lignin‐like polymeric substances (SBO) isolated from the alkaline hydrolysates of composted biowastes are promising chemical auxiliaries for multiple uses. They have good surfactant properties. Their black color spoils their performance in detergency and dyeing. Ozonization of SBO is reported now to yield bleached biosurfactants with improved performance. The work was performed, with SBO obtained from composted gardening residues, alone or mixed with kitchen wastes. They were dissolved in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 38 publications
6
32
0
Order By: Relevance
“…The results obtained in the authors’ previous and present work show that mild chemical hydrolysis and oxidation at room or 60 °C temperature may be well integrated with biochemical processes to valorise biomass as renewable alternative to fossil feedstock more than incineration or high temperature hydrothermal hydrolysis, oxidation and pyrolysis. In the present work, focusing on fermented MBW, it is shown that room temperature oxidation allows improving the performance and value of biopolymers obtained by 60 °C hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results obtained in the authors’ previous and present work show that mild chemical hydrolysis and oxidation at room or 60 °C temperature may be well integrated with biochemical processes to valorise biomass as renewable alternative to fossil feedstock more than incineration or high temperature hydrothermal hydrolysis, oxidation and pyrolysis. In the present work, focusing on fermented MBW, it is shown that room temperature oxidation allows improving the performance and value of biopolymers obtained by 60 °C hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The present paper reports further work addressing the following aspects, which were not covered before. In the previous work, ozonisation of CP SBP was carried in alkaline water solution only at 48 h gas‐liquid contact time while ozonisation of D SBP was not investigated. The comparison of the ozonisation substrates was particularly important as D SBP was expected to yield better surfactants.…”
Section: Lignin Chemical Processesmentioning
confidence: 99%
See 3 more Smart Citations